ANALISIS USAHATANI DAN PEMASARAN BAWANG MERAH DI KABUPATEN TANGGAMUS - Reza Kesuma; Wan Abbas Zakaria; Suriaty Situmorang (Lampung University, 2016)
This study aims to analyze (1) onion farm income and (2) efficiency of onion marketing system. Research was conducted in Tanggamus Regency which chosen purposely and total of samples was 35 farmers and 16 traders in marketing system. Sampling methods of farmers was used by census method, whereas the sampling method of marketing system was used by snowball method. Data collection was conducted in October 2014 until February 2015. Analysis methods used in this research are the analysis of quantitative (statistical) and qualitative (descriptive). The research result showed that (1) onion farm in Tanggamus Regency economically advantageous, base on the value of total cost R/C ratio > 1, on the first crop season of 1,73. (2) The marketing system of the onion in Tanggamus was not efficient due to the margin profit ratio in each marketing organization have not spread evenly, and the price difference (margin) in each marketing organization was too large, although the value of the producer share was quite large, with appromiximately 61,5%-76,9%. Key words: income, marketing, onion farm